Charging performance of S-shaped permanent magnet double stator generator for hydro turbine application - Misron, Norhisam; Ibrahim, Nur Amira; Ahmad Rashidi, Adam Adzrin Syah; Hairul Nizam, Hairul Faizi (2024)
During the past few years, the hydro turbine with double stator generators system performance analytical area has gathered considerable attention and becomes an important research segment within the renewable energy. Various works have been done on various types of dual stator generators for different renewable energy systems. For instance, there have been researches on the design and performance evaluation of dual stator axial flux permanent magnet generators used in marine current turbines [10]. The existence of two stators is beneficial but is also accompanied by issues like variation in torque ratios which impact the rotor maglev forces [12]. Nonetheless, the double stator generator system demonstrated superior efficiency and performance compared to single stator systems.